Analysis of the Implementation Regulations for Police Actions as Law Enforcement of Corruption Cases Constitutional Court - Sacipto, Rian; Prasetyo, Teguh; Mashdurohatun, Anis; Ciptono, (International Journal of Psychosocial Rehabilitation, 2020)
Realizing an Indonesian law state, by upholding justice without differentiating power and authority to realize the legal ideals, is a mandate from the opening of the 1945 Constitution of the Indonesian state. Regulations stating police actions against Constitutional Court judges who commit unusual acts are deemed to be an obstacle to the existence of the rules established by the state constitution so that there are weaknesses that affect the police action rules against Constitutional Court Judges that damage their passion for the problems of corruption that have occurred in Indonesia. The writing of this scientific study aims to uncover and analyze and expect changes in the rules of police action against judges of the Constitutional Court who commit acts of corruption based on justice values to be able to implement appropriate law enforcement without distinguishing the authority and power possessed by state administrators so that there are no obstacles in the process of law enforcement. Several theories are used in the analysis of the framework and methods of thinking of scientific studies by including justice theory, rule of law theory and approach methods that are sourced from primary and secondary data obtained through interviews and conducting literature studies, so as to produce studies that can be analyzed by concluding that it is necessary the change to article 6 Paragraph (2) of Law Number 24 Year 2003 regarding the Constitutional Court explaining the relevant authority in the regulation of the police to act against the constitutional judges who are proven guilty or acts that violate the law without the permission of the President or the Attorney General so that the purpose of the law can be done without distinguishing the authority possessed by each law enforcement agency so that it runs well without any obstacles or complicated processes.